Factors Related to Clean and Healthy Living Behavior in State Elementary School Students in Padang City - Susiyanti; Fauzan Ma'ruf; Wahyu Putriyantari (Miracle Journal Get Press, 2024)
Over 90% of elementary school-age children and over 80% of children younger than secondary school-age children are enrolled in schools globally. Early school health promotion will benefit kids, their families, friends, and the community at large (WHO and UNESCO, 2018). According to the Padang City Health Office's annual report for 2021, Puskesmas Lapai has the lowest percentage of families with clean and healthy habits  6.7% of all sub-districts and puskesmas in Padang City. The aim of this study was to identify the variables linked to Padang City primary school kids' clean and healthy living practices. This type of research is quantitative with an analytic approach and cross sectional design. The population in this study were all students of SD totaling 192 people. The sample was taken as many as 85 respondents. The sampling method was purposive sampling. Data collection through interviews and observations. Data were analyzed univariately and bivariately using the chi square test. The results showed that 56.6% of respondents had poor hygiene behavior, low knowledge 65.9%, and poor teacher role 60.0%. There is a significant relationship between knowledge and clean and healthy living behavior (p-value=0.024) and there is no significant relationship between the role of the teacher and clean and healthy living behavior (p-value=0.562). Increase educational programs on clean and healthy living behaviors for the community as a whole, including increased knowledge. There is also a need to evaluate and improve the role of teachers in educating clean and healthy behaviors through better training and support.